Circulating Hybrid Cells Join the Fray of Circulating Cellular BiomarkersSummary - Thomas L. Sutton; Brett S. Walker; Melissa H. Wong (Cellular and Molecular Gastroenterology and Hepatology, 2019)
Gastrointestinal cancers account for more cancer-related deaths than any other organ system, owing in part to difficulties in early detection, treatment response assessment, and post-treatment surveillance. Circulating biomarkers hold the promise for noninvasive liquid biopsy platforms to overcome these obstacles. Although tumors shed detectable levels of degraded genetic material and cellular debris into peripheral blood, identifying reproducible and clinically relevant information from these analytes (eg, cell-free nucleotides, exosomes, proteins) has proven difficult. Cell-based circulating biomarkers also present challenges, but have multiple advantages including allowing for a more comprehensive tumor analysis, and communicating the risk of metastatic spread. Circulating tumor cells have dominated the cancer cell biomarker field with robust evidence in extraintestinal cancers; however, establishing their clinical utility beyond that of prognostication in colorectal and pancreatic cancers has remained elusive. Recently identified novel populations of tumor-derived cells bring renewed potential to this area of investigation. Cancer-associated macrophage-like cells, immune cells with phagocytosed tumor material, also show utility in prognostication and assessing treatment responsiveness. In addition, circulating hybrid cells are the result of tumor–macrophage fusion, with mounting evidence for a role in the metastatic cascade. Because of their relative abundance in circulation, circulating hybrid cells have great potential as a liquid biomarker for early detection, prognostication, and surveillance. In all, the power of the cell reaches beyond enumeration by providing a cellular source of tumor DNA, RNA, and protein, which can be harnessed to impact overall survival. Keywords: Fusion Hybrid, CAML, CHC, Liquid Biopsy, Macrophage